(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
A series of Ni(II) complexes (NiL1-NiL5) have been synthesized from macrocyclic Schiff base ligands (L1-L5) were obtained from condensation of 4-aminoantipyrine derivative (L) with different diamines and hydrazides. All these compounds were well characterized by elemental, spectral analysis(mass, IR, 1H-NMR, electronic), magnetic suseceptibility, molar conductance and thermal studies. Macrocyclic Schiff bases are tetradentate with N4 donor system around the metal ion.Octahedral geometry have been assigned for all complexes. All ligands and complexes were examined for antibacterial activity and found that complexes were more potent when compared to ligands.